Dual-gate polysilicon nanoribbon biosensors enable high sensitivity detection of proteins. (8th March 2016) - Zeimpekis, I; Sun, K; Hu, C; Ditshego, N M J; Thomas, O; de Planque, M R R; Chong, H M H; Morgan, H; Ashburn, P
Abstract: We demonstrate the advantages of dual-gate polysilicon nanoribbon biosensors with a comprehensive evaluation of different measurement schemes for pH and protein sensing. In particular, we compare the detection of voltage and current changes when top- and bottom-gate bias is applied. Measurements of pH show that a large voltage shift of 491 mV pH −1 is obtained in the subthreshold region when the top-gate is kept at a fixed potential and the bottom-gate is varied (voltage sweep). This is an improvement of 16 times over the 30 mV pH −1 measured using a top-gate sweep with the bottom-gate at a fixed potential. A similar large voltage shift of 175 mV is obtained when the protein avidin is sensed using a bottom-gate sweep. This is an improvement of 20 times compared with the 8.8 mV achieved from a top-gate sweep. Current measurements using bottom-gate sweeps do not deliver the same signal amplification as when using bottom-gate sweeps to measure voltage shifts. Thus, for detecting a small signal change on protein binding, it is advantageous to employ a double-gate transistor and to measure a voltage shift using a bottom-gate sweep. For top-gate sweeps, the use of a dual-gate transistor enables the current sensitivity to be enhanced by applying a negative bias to the bottom-gate to reduce the carrier concentration in the nanoribbon. For pH measurements, the current sensitivity increases from 65% to 149% and for avidin sensing it increases from 1.4% to 2.5%.